دور استراتيجية التدريب في تطوير الموارد البشرية: دراسة حالة شركة سكر كنانة المحدودة السودان 2019م - د. الهادي سليمان إسحق عبد الله; محمد مسعود محمد ادريس (White Nile Journal for Studies and Research, 2019)
The study is to examined the role of training strategy in the development of human resources case study of Kenana Sugar Company. This study aims to identify the impact of human resources training development strategies in the industrial sectors. The problem of the study was What is the role of training strategy in the development of human resources The study assured that there was statistically significant relationship between training strategy and human resources development The study related on the descriptive analytical approach The most important findings of the study are Training improves manpower management skills and the available physical capabilities in order to reach the highest possible productivity at the lowest cost. Training leads to increase in the capacity of the organized component in rational decision making. The study recommended the followings Attention in assessing and measuring the return of training according to specfic mechanism and measures to identify the weaknesses and strengths in directing the training activity to ensure feasibility of training for the company and the employees. Before defining training programs. studies should be conducted to reflect the real and actual organization and indvidual needs. Need to evaluate the level of individuals before and after the training courses in order to determine the magnitude change in their abilities and skills. Training must be linked with a practical side of the work in order to achieve the objectives of the traning process.